BIOACTIVE COMPOUNDS FROM PURPLE ROSELLE CALYX (HIBISCUS SABDARIFFA L.) EXTRACT USING MULTISTAGE COUNTERCURRENT METHOD - Meilya Suzan Triyastuti; Nadiem Anwar (Media Gizi Indonesia, 2022)
Multistage Countercurrent Extraction (MCE) is a new extraction technique used to extract bioactive compounds (anthocyanin, quercetin, antioxidants) from purple roselle calyxes (Hibiscus sabdariffa L.). This study of purple roselle calyxes extract with three-stage MCE was carried out at a comparison of roselle calyxes and distillation water solvent 1:10, extraction temperatures of 50°C, 60°C, 70°C and extraction time of 15, 30, 45 minutes. Purple roselle calyxes using the MCE method contained the highest anthocyanin content of 2815,43 mg/L, quercetin content 59,25 mg/L, and antioxidant capacity 197,6 ppm. The results showed that the content of bioactive compounds increased by increasing the extraction temperature and extraction time. MCE is an efficient technique for extracting bioactive compounds from roselle calyxes. Roselle calyxes that are rich in antioxidants have the potential as a good food colorant andnatural antioxidants.